2006
DOI: 10.1038/sj.bjp.0706673
|View full text |Cite
|
Sign up to set email alerts
|

A novel steroid‐like compound F90927 exerting positive‐inotropic effects in cardiac muscle

Abstract: 1 Here we report a novel steroid-like compound F90363, exhibiting positive inotropy in vivo and in vitro in various cardiac muscle preparations. 2 F90363 is a racemic mixture composed of the stereoisomers (À)-F90926 and ( þ )-F90927. Only F90927 exerted positive inotropy, while F90926 induced a weak negative inotropy, but only at concentrations 10 3 times higher than F90927 and most likely resulting from an unspecific interaction. 3 The rapid time course of the action of F90927 suggested a direct interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In guinea pigs, treatment with F90927 increased systemic arterial pressure without leading to arrhythmias, even at high concentrations (Pignier et al 2006) (Fig. 4).…”
Section: Pharmacologymentioning
confidence: 94%
See 2 more Smart Citations
“…In guinea pigs, treatment with F90927 increased systemic arterial pressure without leading to arrhythmias, even at high concentrations (Pignier et al 2006) (Fig. 4).…”
Section: Pharmacologymentioning
confidence: 94%
“…To identify the molecular mechanism underlying the positive inotropy of F90927, electrophysiological experiments were carried out on isolated cardiac myocytes. Whole‐cell voltage‐clamp experiments in combination with laser‐scanning confocal Ca 2+ imaging enabled the identification of the L‐type Ca 2+ channel as the main target and it was shown that F90927 enhances beat‐to‐beat Ca 2+ cycling in myocytes (Pignier et al 2006) (Fig. 2A).…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some cardiotonic steroids derivatives have been prepared; for example, the strophanthidin (steroid derivative) increase the force of contraction by changes in the calcium levels in cardiac purkinje fibers [7]. Also, there are studies that show the synthesis of a steroid derivative (F90927) which exerts a positive inotropic activity in cardiac muscle via activation of the L-type calcium channel [8]. Other study indicates that 14b-hydroxyprogesterone increases the contractility of isolated cardiac tissue via glycoside receptor [9].…”
Section: Introductionmentioning
confidence: 99%
“…[14] Other data showed the total synthesis of a steroid derivative (F90927) which exerted positive inotropic effect on cardiac muscle. [15] Also, the androstane-3, 6,17-trione(E,Z)-3-(2aminoethyl)oxime was prepared via reaction of a ketosteroid with (O-aminoalkyl)hydroxylamine which showed positive inotropic in vitro. [16] In addition, recently a dihydrotestosterone derivative was prepared via reaction of dihydrotestosterone with an oxazin-pyrazol-diamine complex which exert a positive inotropic activity on isolated heart.…”
Section: Introductionmentioning
confidence: 99%